Initial evaluation of the efficacy and safety of in-hospital expandable hemostatic minisponge use in penetrating trauma. Issue 3 (March 2019) - Warriner, Zachary; Lam, Lydia; Matsushima, Kazuhide; Benjamin, Elizabeth; Strumwasser, Aaron; Demetriades, Demetrios; Inaba, Kenji
Abstract : BACKGROUND: Hemorrhage remains the leading cause of preventable death after trauma. The XSTAT expandable minisponge hemostatic device was developed for the control of severe, life-threatening bleeding from junctional wounds not amenable to tourniquet application. This is an initial report of the clinical use of this novel method of hemorrhage control for civilian penetrating injury. METHODS: A review of trauma admissions at a high-volume Level I trauma center was performed from July 2016 to November 2017. All patients sustaining penetrating trauma with active hemorrhage were evaluated for XSTAT use. Ten device deployments occurred during this time. Each deployment was reviewed in detail, capturing patient and injury data, efficacy of hemorrhage control, and evaluation of any potential device or treatment related complications. RESULTS: Six thousand three hundred sixty-three trauma admissions were reviewed with 22.1% sustaining a penetrating mechanism of injury. XSTAT was deployed in 10 (0.7%) penetrating trauma admissions with a mean age of 38.3 (range, 16–59) years, systolic blood pressure (SBP) of 126.7 (range, 74–194) mm Hg, Glasgow Coma Scale (GCS) score of 14.5 (range, 13–15), and New Injury Severity Score (NISS) of 9.5 (range, 1–27). Eight patients had an identifiable arterial injury; the remainder had vein or soft tissue bleeding. Overall, half were junctional injuries. XSTAT was able to stop bleeding in nine of ten patients on the first deployment, with the remaining patient requiring one repeat injection. Dwell times ranged from 1 hour to 40 hours (median, 15 hours). There were no technical device failures or embolic complications. Retained sponges were identified in two patients on initial postremoval x-rays following wound exploration for definitive hemorrhage control and sponge removal. No patient died during the study period. CONCLUSION: XSTAT use appears safe. It is rapid, reliable, and provides a high degree of hemorrhage control on first deployment. Sponge removal should always be followed by radiographic clearance. For patients with hemorrhage from cavitary wounds not amenable to tourniquet placement, this device was effective. Further study is warranted as XSTAT use becomes more widespread. LEVEL OF EVIDENCE: Therapeutic study, level V.